Sistem Informasi Geografis Izin Lokasi dan IPPT Kota Bandung Menggunakan Mapserver dan PostGIS - Ari Bratasena; Gede Karya (UIN Sultan Syarif Kasim Riau, 2012)
Geographic Information Systems (GIS) application is currently growing, and manyhave started to use for certain purposes. GIS itself is a computer-based system thatfacilitates data entry, data analysis and presentation of data, especially in the case whendealing with spatial data. Today there are many applications are used to develop GIS. Oneof GIS application is MapServer. MapServer is a open source software development environment that can be used to develop web based applications involving the display of spatialdata. As for the storage of spatial data can use PostGIS database. PostGIS is thedevelopment of PostgreSQL that can store and process spatial data type. In this paperwill be described GIS applications using MapServer and PostGIS to assist Dinas TataRuang dan Cipta Karya in terms of doing the analysis Location Permit and the LandUse Permit. The results of this research is expected that each applicant whowants to makeLocation Permit or Land Use Permit in accordance with therules that have been defined.Keywords: Geographic Information Systems, MapServer, PostGIS, Location Permit, Land Use Permit